Implementasi Wireless Sensor Network Berbasis LoRa Master Slave - Asma Amaliah; Sahbuddin Abdul Kadir; Alviany Saldina; Reski Amelia (Jurnal Mosfet, 2025)
Long Range (LoRa) is a wireless communication technology using Chirp Spread Spectrum (CSS) that allows for sending low-power long-distance data via the ISM (Instrumentation Science and Medical) band. This study aims to utilize LoRa technology with a Master Slave communication model combined with a Wireless Sensor Network (WSN). The devices used in this study are LoRa, ESP32 and MQ135 sensors. The MQ135 sensor functions to measure ambient air quality. Then data from the sensor is sent using the LoRa module via 3 nodes to the master node. The OLED display is used to display the results of sensor readings in the form of CO and CO2 values. Then ESP 32 functions to process data from the sensor and regulate system performance. The air quality detection system was tested under two different conditions, areas with and without obstacles. Areas with obstacles is located on Campus 1 PNUP. Areas without obstacles is located on Mandai Underpass. The results of the tool test show that the area with obstacles located at Campus 1 PNUP, the furthest distance that can still be reached by LoRa is 100 meters. For the second location of the Mandai Underpass, the furthest distance LoRa still communicates is 140 meters.